Administrative Accountability of Public Officials for Criminal Acts of Corruption from the Perspective of State Administrative Law - Alpi Sahari (Universitas Muhammadiyah Sumatera Utara, 2026)
Corruption is a social ill that undermines the people's welfare and hinders the implementation of national development. It also damages the image of a clean and dignified state apparatus, disregards morals, and damages the image and quality of people and the environment. Corruption in Indonesia has become widespread in all aspects of society. Corruption is considered to be widespread and is carried out by officials at various levels, including all levels of local government. Regulations related to corruption in Indonesia are contained in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption. In addition, the Criminal Code also outlines regulations related to corruption. Administrative sanctions for corrupt public officials include dishonorable dismissal from office, revocation of pension and allowance rights, and a ban on holding public office for a certain period. These sanctions can be supplemented by other sanctions such as fines, compensation, or publication in the mass media if the sanctions are severe